Atanasio Herranz (comp.), El español hablado en Honduras. Editorial Guaymuras, Tegucigalpa, 1990; 298 pp. - Lara, Luis Fernando (El Colegio de México, 1993)
Se reseñó el libro: El español hablado en Honduras.